Pedagogical conditions for the organization of professional adaptation future music teacher in higher education (Pedagogy of Higher and Secondary Education, 2021)
Is this article the expediency of system approach to management by adaptation process of future musicteacher. It is analyzed the conception of projecting and prognosis of profile education in conditions of conceptual and figurative cognition unity, creative and intuitive development.
Keywords: teacher of music; adaptation; system approach; creativity; intuition; prognosis; projecting